2009
DOI: 10.1080/09540120903012601
|View full text |Cite
|
Sign up to set email alerts
|

Life in institutional care: the voices of children in a residential facility in Botswana

Abstract: As a result of the HIV/AIDS pandemic, there are now more than 12 million orphans in sub-Saharan Africa. The majority of these children have been absorbed into their extended families. A minority of AIDS orphans and other vulnerable children are living in residential care facilities. Although concerns have been raised regarding the care received in such facilities, very little is known about children's perspectives on their own experiences residing in these institutions. As part of an ongoing initiative to bett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 34 publications
1
23
0
Order By: Relevance
“…Data from other countries have found similar prevalences. Among 232 child and youth residents in a Botswana residential care facility, 28% were placed for neglect (versus 21% in this study) and 8% for abuse (same in this study) (Morantz & Heymann, 2010). An audit of 1007 children and youth living in 28 institutions in South Africa revealed that 30% had experienced abuse and/or neglect, and 24% had been abandoned (Meintjes et al 2007).…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Data from other countries have found similar prevalences. Among 232 child and youth residents in a Botswana residential care facility, 28% were placed for neglect (versus 21% in this study) and 8% for abuse (same in this study) (Morantz & Heymann, 2010). An audit of 1007 children and youth living in 28 institutions in South Africa revealed that 30% had experienced abuse and/or neglect, and 24% had been abandoned (Meintjes et al 2007).…”
Section: Discussionmentioning
confidence: 56%
“…Poverty-related conditions seem to underlie much of the orphanhood experience (Foster et al, 1997; Heymann et al, 2007; Miller et al, 2007; Nyambedha et al, 2003; Oleke et al, 2005; Powell et al, 2004; UNICEF et al, 2006). In the file review carried out at a residential care facility in Botswana, 38% of children and youth had been admitted for poverty-related conditions (Morantz & Heymann, 2010). Meinjtes et al (2007) in their study of institutions in South Africa maintained that “the underlying reason for admission is destitution.” A high prevalence of destitution was also found in this study (60% of child and youth residents).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of corporal punishment is an ineffective means of discipline, is linked to child abuse, may have long-term negative effects on the child [44-47], and violates the Convention on the Rights of the Child Article 19 and 37 [30] and therefore is a fundamental breach of children’s human rights [48]. Third, despite reports in other sub-Saharan African settings stating that children in institutional care lack links to family, and community [26,27,49], CCI’s and CBO’s in UG County worked to facilitate family connections through their programs and ensuring that children in their care have knowledge of and where possible, contact with, their families. Fourth, very few children in both institutional and family-based care have birth certificates and therefore are lacking their right to their identity.…”
Section: Discussionmentioning
confidence: 99%
“…Despite early catastrophic predictions (Poonawalla and Cantor 1991; Barnett and Blaikie 1992; United Nations Children’s Fund 2003), however, there has not been the anticipated surge in Western-style orphanages or child-headed households. It is thought that fewer than five per cent of orphans live on the streets or in institutions although this has increased in the most severely affected countries (Monasch and Boerma 2004; Powell et al 2004; Beard 2005; United Nations Children’s Fund 2005; UNICEF, UNAIDS, and PEPFAR 2006; Morantz and Heymann 2010). Furthermore, a recent study of child-headed households in Zimbabwe found that few of these households comprised orphans, which challenges the idea that such households reflect the absorptive capacity of the extended family (Ciganda et al 2010).…”
Section: Introductionmentioning
confidence: 99%